Preliminary study on overproduction of reactive oxygen species by neutrophils in diabetes mellitus - Ridzuan, Noridzzaida; John, Cini Mathew; Sandrasaigaran, Pratheep; Ramasamy, Rajesh (Baishideng Publishing Group, 2016)
Aim: To assess the amount and pattern of reactive oxygen species (ROS) production in diabetic patient-derived neutrophils. Methods: Blood samples from type 2 diabetes mellitus (DM) patients and volunteers (controls) were subjected to neutrophil isolation and the assessment of neutrophil oxidative burst using chemiluminescence assay. Neutrophils were activated by using phorbol myristate acetate (PMA) and neutrophils without activation were kept as a negative control. The chemiluminescence readings were obtained by transferring cell suspension into a 1.5 mL Eppendorf tube, with PMA and luminol. Reaction mixtures were gently vortexed and placed inside luminometer for a duration of 5 min. Results: Our results showed that in the resting condition, the secretion of ROS in normal non-diabetic individuals was relatively low compared to diabetic patients. However, the time scale observation revealed that the secreted ROS declined accordingly with time in non-diabetic individuals, yet such a reduction was not detected in diabetic patients where at all the time points, the secretion of ROS was maintained at similar magnitudes. This preliminary study demonstrated that ROS production was significantly higher in patients with DM compared to non-diabetic subjects in both resting and activated conditions. Conclusion: The respiratory burst activity of neutrophils could be affected by DM and the elevation of ROS production might be an aggravating factor in diabetic-related complications.